Development of a compact and robust kinetic mechanism for furan group biofuels combustion in internal combustion engines. (15th August 2021) - Wu, Shaohua; Tay, Kun Lin; Li, Jing; Yang, Wenming; Yang, Shiliang
Graphical abstract: Abstract: A compact kinetic reaction mechanism for simulating the oxidation of the unsaturated furanic fuels including furan, 2-methylfuran (MF2) and 2, 5-dimethylfuran (DMF) is proposed in this work. The mechanism is developed by integrating the major reaction pathways for the three furanic fuel components into a toluene reference fuel reaction mechanism. The sub-mechanism describing the formation and growth of polycyclic aromatic hydrocarbons up to pyrene is also incorporated so that the prediction of soot formation is enabled. The major reaction pathways for these furanic fuels are derived from the detailed furanic fuel reaction mechanism in the literature via a systematic selection and extraction procedure. An advanced genetic algorithm is applied to automatically optimize the rate parameters for the major furanic fuel reaction pathways. In addition, a simplified empirical soot model is embedded in the mechanism for simulating the soot formation process in the oxidation of the furanic fuels. The resulting mechanism, consisting of 145 species and 643 reactions, has been evaluated against the ignition delays, speciation profiles, laminar flame speeds as well as the soot mass measured from the combustion of the furanic fuels in the literature. The simulation results in general match satisfactorily well with the experimental data, suggesting the high performance of the proposed mechanism. The performance of the reaction mechanism for engine combustion simulation is also tested. A four-cylinder compression ignition engine is simulated using a coupled KIVA4-CHEMKIN code package. The influences of DMF on the engine combustion characteristics and soot emissions are investigated.